On Being the Editor of AJS - Abbott, Andrew (Serendipities. Journal for the Sociology and History of the Social Sciences, 2018)
Andrew Abbott, editor of the American Journal of Sociology from 2000 to 2016, explains in this interview the role of an editor, discusses criticisms against flagship journals, relativizes the influence of editors, praises colleagues participating in the peer review process and offers a look at the backstage of academic publishing.